2015-04-19T10:41:29+05:30

### This Is a Certified Answer

Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.
x² + 5x +6

⇒x² + (2+3)x + 6

⇒x² + 2x + 3x + 6

⇒x(x+2) +3(x+2)

⇒(x+3)(x+2)

therefore,

either,        or,

x+3=0        x+2=0

x=-3           x=-2
thank you
welcome dr
ok
2015-04-19T10:41:49+05:30

### This Is a Certified Answer

Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.
x²+5x+6 can be written as :-
x² + 2x + 3x + 6
= x(x+2) + 3(x+2)
= (x+3)(x+2) [Taking x+2 as common]

Hope that helps !!
Plz pick it as best if it was helpful !! :)